2014
DOI: 10.1179/0001551214z.00000000030
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with lenalidomide (Revlimid®), cyclophosphamide (Endoxan®) and prednisone (REP) in relapsed/refractory multiple myeloma patients: results of a single centre retrospective study

Abstract: Lenalidomide (Revlimid®) combined with intermittent dexamethasone (the RD regimen) is one of the current standards for treatment of patients with relapsed/refractory multiple myeloma (MM). However, since the disease in the majority of patients will become resistant to RD, or treatment with RD needs to be discontinued due to side effects, we evaluated the combination lenalidomide, low-dose oral cyclophosphamide, with prednisone (REP) in patients with relapsed/refractory MM previously exposed to RD. For this pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Furthermore, a retrospective analysis showed high efficacy ($ PR: 68%) and good tolerability of lenalidomide, low-dose cyclophosphamide, and prednisone in relapsed/refractory MM patients who were previously exposed to lenalidomide-dexamethasone (39% lenalidomide refractory). 43 Similarly, it has recently been shown that addition of cyclophosphamide to pomalidomide and dexamethasone in lenalidomide-refractory MM increases the ORR from 39% to 65% and median PFS from 4.4 to 9.5 months. 44 Larocca et al also showed that pomalidomide in combination with cyclophosphamide-prednisone is effective and well tolerated in lenalidomide-and bortezomib-refractory MM patients ($ PR: 50%; median PFS: 8.6 months).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a retrospective analysis showed high efficacy ($ PR: 68%) and good tolerability of lenalidomide, low-dose cyclophosphamide, and prednisone in relapsed/refractory MM patients who were previously exposed to lenalidomide-dexamethasone (39% lenalidomide refractory). 43 Similarly, it has recently been shown that addition of cyclophosphamide to pomalidomide and dexamethasone in lenalidomide-refractory MM increases the ORR from 39% to 65% and median PFS from 4.4 to 9.5 months. 44 Larocca et al also showed that pomalidomide in combination with cyclophosphamide-prednisone is effective and well tolerated in lenalidomide-and bortezomib-refractory MM patients ($ PR: 50%; median PFS: 8.6 months).…”
Section: Discussionmentioning
confidence: 99%
“…They showed a median PFS of 12.2 months and a OS at 1 year of 92.9%. Zelis et al retrospectively evaluated REP regimen in RRMM previously exposed to Rd, with a ORR of 63%, good tolerability but a PFS of only 6 months. Reece et al also described the safety and the efficacy of REP regimen in this subset of patients, with good responses (ORR 94%) and acceptable tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the new or emerging standards of care for second-line treatment are Rd-based combinations (e.g., carfilzomib-Rd [KRd], ixazomib-Rd [IRd], elotuzumab-Rd, daratumumab-Rd), although clinical trial data regarding their efficacy and safety in patients previously treated with lenalidomide are currently lacking; however, a retrospective analysis suggests that KRd may be effective in this setting [84]. Treatment re-intensification by combining lenalidomide with conventional cytotoxic agents is another second-line option that has shown promise [85][86][87]. In the phase 1/2 REPEAT trial, in which patients with lenalidomide-refractory MM received lenalidomide, low-dose cyclophosphamide, and prednisone until disease progression, 67% of patients achieved a partial response or better, including 23% VGPR and 5% CR [85].…”
Section: Impact Of Long-term Lenalidomide Therapy On Subsequent Treatmentioning
confidence: 99%